Projection of HIV/AIDS Mortality in Adamawa State through the Lee-Carter Model: Strides toward SDG-3 - Nuhu, Wasinda Bassi; Stephen, Hyelda; Abdulkadir, Usman Almujaddid; Sirante, Richard Martins; Sirante, Francisca Jugivetje (International Journal of Multidisciplinary Approach Research and Science, 2025)
Globally, HIV/AIDS remains a significant health concern, with profound impacts in developing nations, including Nigeria. This study aims to project mortality among HIV patients in Adamawa State using the Lee-Carter model to assess progress towards the third Sustainable Development Goal (SDG-3) - terminating AIDS by 2030. Mortality data for 2011-2020 on HIV patients aged 15-59 years receiving antiretroviral therapy (ART) was obtained from Adamawa State AIDS control database. The Lee-Carter model, using the Singular Value decomposition (SVD) for parameter estimation was fitted to estimate age-specific parameters. The time series component was forecast using ARIMA(0,1,0). Mortality data from 2011 to 2020 revealed a substantial 296% reduction in mortality, a testament to government and NGO interventions. The study delineates varied age group responses to improvements in mortality rates, pinpointing ages 55-59 as the most affected, while ages 15-19 exhibit the lowest mortality rates. Furthermore, individuals aged 20-24 show heightened responsiveness to general mortality improvements compared to other age cohorts. This work substantiates that Adamawa State has achieved substantial progress, exceeding the SDG-3 target of a 90% decline in HIV/AIDS patient mortality rate, setting a promising trajectory towards an AIDS-free society by 2030. However targeted strategies are still needed for older patients.